(untitled) (Journal of Medical Sciences, 2024)
Aim: To describe the clinical features and the presenting symptoms of HS purpura and HS nephritis in Misrata Medical Center and evaluate prognosis of the disease. Materials and methods: A retrospective study of children diagnosed as HS purpura in Misrata Medical Center (single center). All patient’s data were collected and reviewed from follow-up records in pediatric nephrology Outpatient Clinic in Misrata Medical Center in the period between November 2016 and May 2021. Results: In this study, 55 HSP patients were included, 37 patients were boys and 18 were girls giving a male to female ratio of 2.05: 1. The mean age was 5.8 years (range of 1-12). 20 cases presented in spring season (36%), while 19 cases in winter (34%) and 16 cases in autumn. No cases presented in summer season. The most common manifestation was skin rash (100%). 12 cases (21.82%) had renal involvement (nephritis). The most common HS Nephritis manifestation was microscopic hematuria in 21% of cases then proteinuria (11%) and macroscopic hematuria (7%). Only one case had hypertension (1.82%). All patients had normal renal function tests. No cases progressed to End Stage Renal Disease (ESRD). All cases were self-limiting (complete disappearance of renal manifestations occurred within 3 months) except one case (1.82%) that had persistent proteinuria after 1 year of follow-up, she was a 12-year-old girl, presented with headache, edema, skin rash, high BP, gross hematuria and proteinuria. Conclusion: From our review for a single center we conclude that HSP is a self- limiting disease with good prognosis. Most cases occur in spring and winter. HS Nephritis occurred in 22% of cases.